A phase I/II exploratory clinical trial for intracordal injection of recombinant hepatocyte growth factor for vocal fold scar and sulcus. (25th December 2017) - Hirano, Shigeru; Kawamoto, Atsuhiko; Tateya, Ichiro; Mizuta, Masanobu; Kishimoto, Yo; Hiwatashi, Nao; Kawai, Yoshitaka; Tsuji, Takuya; Suzuki, Ryo; Kaneko, Mami; Naito, Yasushi; Kagimura, Tatsuo; et al.
Abstract: Vocal fold scar and sulcus are intractable diseases with no effective established treatments. Hepatocyte growth factor (HGF) has preclinically proven to have potent antifibrotic and regenerative effects on vocal fold scar. The current Phase I/II clinical trial aims to examine the safety and effectiveness of intracordal injection of a recombinant human HGF drug for patients with vocal fold scar or sulcus. This is an open‐label, dose‐escalating, first‐in‐human clinical trial. Eighteen patients with bilateral vocal fold scar or sulcus were enrolled and divided into three groups: Step I received 1 μg of HGF per vocal fold; Step II received 3 μg of HGF; and Step III received 10 μg of HGF. Injections were administered once weekly for 4 weeks. The protocol treatment was performed starting with Step I and escalating to Step III. Patients were followed for 6 months post‐treatment. Local and systemic safety aspects were examined as primary endpoints, and therapeutic effects were assessed as secondary endpoints using voice handicap index‐10; maximum phonation time; vocal fold vibratory amplitude; grade, rough, breathy, asthenic, strained scale; and jitter. The results indicated no serious drug‐related adverse events in either the systemic or local examinations. In whole‐subject analysis, voice handicap index‐10, vocal fold vibratory amplitude, and grade, rough, breathy, asthenic, strained scale were significantly improved at 6 months, whereas maximum phonation time and jitter varied. There were no significant differences in phonatory data between the step groups. In conclusion, intracordal injection of a recombinant human HGF drug was safe, feasible, and potentially effective for human patients with vocal fold scar or sulcus.